A bi-level model for GHG emission charge based on a continuous distribution of travelers' value of time (VOT). (August 2016) - Zhao, Laijun; Xu, Xiang; Gao, H. Oliver; Wang, Jiajia; Xie, Yujing
Highlights: We introduce continuous VOT of travelers into bi-level model for emission charge. It is unexpected that the higher VOT does not necessarily bring higher emission charge. In some cases, emission charge can both improve the efficiency of transport network and reduce GHG. Abstract: Transportation is an important source of greenhouse gas (GHG) emissions. In this paper, we develop a bi-level model for GHG emission charge based on continuous distribution of the value of time ( VOT ) for travelers. In the bi-level model framework, a policy maker (as the leader) seeks an optimal emission charge scheme, with tolls differentiated across travel modes (e.g., bus, motorcycles, and cars), to achieve a given GHG reduction target by shifting the proportions of travelers taking different modes. In response, travelers (as followers) will adjust their travel modes to minimize their total travel cost. The resulting mode shift, hence the outcome of the emission charge policy, depends on travelers' VOT distribution. For the solution of the bi-level model, we integrate a differential evolution algorithm for the upper level and the "all or nothing" traffic assignment for the lower level. Numerical results from our analysis suggest important policy implications: (1) in setting the optimal GHG emission charge scheme for the design of transportation GHG emission reduction targets, policy makers need to be equipped with rigorous understanding of travelers' VO T distribution and the tradeoffs between emission reduction and system efficiency; and (2) the optimal emission charge scheme in a city depends significantly on the average value of travelers' VOT distribution—the optimal emission charge can be designed and implemented in consistency with rational travel flows. Further sensitivity analysis considering various GHG reduction targets and different VOT distributions indicate that plausible emission toll schemes that encourage travelers to choose greener transportation modes can be explored as an efficient policy instrument for both transportation network performance improvement and GHG reduction.